Social Enterprises in Lithuania: Historical Roots and Current Trends - Urmanavičienė, Audronė; Butkevičienė, Eglė; Erpf, Philipp; Raišienė, Agota Giedrė (Social Enterprise in Central and Eastern Europe, 2021)
This chapter presents an overview of the general Social Enterprise (SE) context in the country, analysing factors that shaped SE development, and discusses three main models of social enterprise in Lithuania, namely work-integration social enterprises, social-business organisations and entrepreneurial non-profit organisations, and their links to the EMES indicators. The Lithuanian Law on Social Enterprises was adopted in 2004 and amended in 2011. In 2019, new initiatives were launched with a view to legally defining and promoting the notions of “social business” and “social enterprise”. The aim of Work-Integration Social Enterprises (WISEs) is the reintegration into work of excluded persons belonging to specific target groups, through production or service-provision activities. The leading players promoting WISEs are business-sector companies. Social-business organisations are businesses in which the social mission is the most important mission, and the main aim is to find solutions for social problems in society.